Gold-Catalyzed Cope Rearrangements - Paroi, Bidisha; Patil, Nitin T. (Synlett, 2024)
Over decades, Cope rearrangements have attracted significant research interest in the field of synthetic organic chemistry relying on their ability to undergo stereoselective structural reorganization. Despite substantial progress, the development of this field remained confined to the use of parent 1,5-hexadienes. Against the backdrop of classical Cope reaction, we report the utilization of unconventional 1,6-heptadienes to develop the arylative Cope rearrangement by harnessing the interplay between the π-activation and cross-coupling reactivity mode of gold complexes. Several mechanistic investigations such as 31P NMR study, HRMS analysis, cross-over experiment, control experiments were performed to support the proposed cyclization-induced [3,3]-rearrangement mechanism in arylative Cope reaction.1 Gold-Catalyzed Cope Rearrangements2 Gold-Catalyzed Arylative Cope Rearrangement3 Conclusion
Keywords: gold catalysis; π-activation; cross-coupling; redox catalysis; Cope rearrangement